EVALUATION FIRMNESS OF VARIETIES OF THE STONE FRUIT CROPS TO ACID RAINS CAUSED WITH AEROSOL FORMING - Харитонов, М. М.; Станкевич, С. А.; Клименко, О. Є.; Хлопова, В. М. (Scientific Progress & Innovations, 2014)
One MPC a steady exceeding in the level of month nitrogen dioxide average concentration in the atmosphere of industrial cities of Dnipropetrovsk region was fixed. Air NO2 content changed from 0,03 to 0,08 mg/m3 in Krivoy Rog and from 0,05 to 0,09 mg/m3 – in Dniprodzerzhinsk and Dnipropetrovsk last years. The data base with remote and ground based sensing of atmosphere pollution with acid aerosols gave possibility to establish level of artificial acid rain forming in model conditions. It was fixed in the experiments different concentrations of aerosols on activity of some components of stone fruit crops antioxidant system for relative firmness of varieties to technogenic stress, to work out the scale of relative firmness of kinds and varieties to acid rains.It was established that on firmness of varieties of to acid rains the stone fruit crops can be disposed in the regression line: plum > myrobalan plum > apricot > pench. Lowest firmness has got varieties early terming of ripening (pench, apricot) in the limits of one kind. An origin took a big place then term of ripening in myrobalan plum. Sometimes the varieties of one fruit crop have distinction to acid rains then other crops. Data obtained allow to manage assortment of firm and relatively firm to air pollution with acid aerosols and acid rains for crops and varieties of Prunus L. in south of Ukraine.